Implementasi Cleanliness, Health, Safety and Environment Sustainability (CHSE) Daya Tarik Wisata Taman Pintar Yogyakarta Tahun 2025 - Utomo, Fadlillah Reo; Kasjono, Heru Subaris; Sugianto, Sugianto; Rois, Ibnu (Pusat Studi Pariwisata Universitas Gadjah Mada, 2026)
The COVID-19 pandemic had a significant impact on the tourism sector in Indonesia. As part of the recovery efforts, the government introduced the Cleanliness, Health, Safety, and Environment Sustainability (CHSE) standards to ensure the safety, health, and comfort of tourists. Taman Pintar Yogyakarta, an educational tourism destination certified with CHSE, has experienced a notable increase in visitor numbers over the past three years. This study aims to examine the implementation of CHSE standards at the tourist attractions within Taman Pintar Yogyakarta in 2025. A descriptive method with a mixed approach was applied, using observation, interviews, and documentation for data collection. The research instrument employed was a checklist based on the Indonesian National Standard (SNI) 9042:2021. The findings revealed that none of the ten tourist attractions at Taman Pintar Yogyakarta fully met all CHSE indicators. Eight attractions fulfilled 48 out of 49 indicators (98%), while the other two fulfilled 47 indicators (96%). The most common shortcomings were related to safety indicators, particularly the unavailability of assembly point maps, as well as cleanliness facilities such as toilets that were not functioning properly.